Evidence and relevance of spatially chaotic magnetic field lines in MCF devices - Firpo, Marie Christine (2017)
Numerical evidence for the existence of spatially chaotic magnetic field lines about the collapse phase of tokamak sawteeth with incomplete reconnection is presented. This uses the results of extensive test particle simulations in different sets of electromagnetic perturbations tested against experimental JET measurements. In tokamak sawteeth, that form a laboratory prototype of magnetic reconnection, the relative magnetic perturbation dB B may reach a few percents. This does not apply to tokamak operating regimes dominated by turbulence where dB B is usually not larger than 10^- 4 . However, this small magnetic perturbation being sustained by a large spectrum of modes is shown to be sufficient to ensure the existence of stochastic magnetic field lines. This has important consequences for magnetic confinement fusion where electrons are dominantly governed by the magnetic force. Indeed some overlap between magnetic resonances can locally induce chaotic magnetic field lines enabling the spatial redistribution of the electron population and of its thermal content. As they are the swiftest plasma particles, electrons feed back the most rapid perturbations of the magnetic field.